(untitled) (NIGERIAN JOURNAL OF PAEDIATRICS, 2024)
Patel A, Owa JA and Harvey D. Summary: Aluminium foil was applied to one or more sides of the incubator to improve the irradiance from phototherapy units. The irradiance, measured at the level where an infant is normally placed, significantly increased when aluminium foil was applied to two or more sides of the incubator, to a maximum of about 30 percent above the initial value without the foil (p<0.001). This was similar to the irradiance obtained with silver swaddler. This method of using aluminium foil can improve the effectiveness of phototherapy units and reduce the need to use multiple phototherapy units.